Деякі аспекти розвитку системи аналізу ризиків порушення митного законодавства - Мороз, Б. І.; Коноваленко, С. М. (НТУ "ХПІ", 2011)
Розглянуто деякі аспекти розвитку автоматизованої системи аналізу ризиків порушення митного законодавства, а саме можливість застосування методів та засобів штучного інтелекту у вигляді нейромережевого моделювання. Описана модель нейронної мережі типу багатошаровий персептрон та використано ітеративний метод навчання з можливістю обходу локальних мінімумів. Іл.: 1. Табл.: 1. Бібліогр.: 11 назв.

It is considered the basic aspects of development of the automated system of the analysis of risks of infringement of the customs legislation, namely possibility of application of methods and artificial intelligence techniques in a kind neuro-network modelling. The model of a neural network of type multilayered perseptron is described and the iterative method of training with possibility of detour of local minima is used. Figs.: 1. Tabl.: 1. Refs.: 11 titles.
Some aspects of development system of the analysis risks infringement of the customs legislation
Keywords: митний контроль; нейронна мережа; багатошаровий персептрон; ітеративний метод; analysis of risks; neural network; perseptron; iterative method